CLASSIFICATION OF TURBIDITY COMPONENTS OF BEVERAGES FROM PLANT RAW MATERIAL - Sergeeva I.Y. (Техника и технология пищевых производств, 2016)
Beverages from plant raw materials are solutions of compounds of various molecular weights. Most extractives of beverages are high molecular weight compounds, which determine a dispersion state of the system. The aim of the research is to develop a classification of turbidity components of beverages as a methodological basis to indicate a method for correcting a process step or a process object when obtaining a high quality product. The methods of analysis and selection, generalization and systematization of information sources, a hierarchical classification method are used. A short description of turbidity components of beverages from plant raw material is given. Some characteristics of beverages from plant raw material as a disperse system, according to the terminology of colloid chemistry, are presented. Classification of turbidity components of beverages is offered using a hierarchical method. This classification is based on structural and technological characteristics of the turbidity components of beverages. It is proposed to subdivide the set of turbidity components of beverages into the following elements: substances of phenolic, protein and carbohydrate nature, metals, oxygen, production microorganisms and complexes of the above components. Signs of classification are marked. The analysis of the value of classification characteristics for the solution of production problems connected with the correction of the qualitative composition of semi-finished or finished beverages and quantitative content of turbidity components is given.